Cone-beam evaluation of pharyngeal airway space in class I, II, and III patients - Castro-Silva, Lucas [UNESP]; Monnazzi, Marcelo Silva [UNESP]; Spin-Neto, Rubens [UNESP]; Moraes, Marcio [UNESP]; Miranda, Sergio [UNESP]; Real Gabrielli, Mario Francisco [UNESP]; Pereira-Filho, Valfrido Antonio [UNESP] (Elsevier B. V., 2015)
The purpose of this study is to make a 3-dimensional (3-D) evaluation of the pharyngeal airway space (PAS) in patients with class I, II, and III malocclusion. Sixty patients were evaluated. The patients were divided in 3 groups according to their occlusion classification. The volume and area of PAS were evaluated using the software Dolphin 3-D Imaging in the preoperative period for orthognathic surgery. PAS volume and area were influenced by different patterns of malocclusion. The mean volume and area for class III patients were statistically bigger than for classes I and II patients (P < .001). There was also a significant difference for volume values between class I and II patients, being the bigger volume for the class I patients (P < .05). It was possible to conclude that the class III patients presented a bigger PAS compared with classes I and II patients.